A participatory framework for prioritizing climate-smart agriculture innovations in rice-based systems: A case study of Mali - Dossou-Yovo, Eliott Ronald; Arouna, Aminou; Benfica, Rui; Mujawamariyac, Gaudiose; Yossad, Rodrigue (Elsevier, 2024)
Alleviating the climate-related constraints faced by agri-food systems in sub-Saharan Africa requires an accelerated adoption of climate-smart agriculture (CSA) innovations by farmers. However, little is known about the best-bet (most appropriate) CSA innovations, and the enabling conditions for their widespread adoption in a given biophysical and socioeconomic context. The objectives of this study were to identify the best-bet CSA innovations and the barriers, incentive mechanisms, and roles of institutions in widespread adoption in the four rice growing environments in Mali (irrigated lowlands, rainfed lowlands, rainfed uplands, and submergence systems). Data were collected from stakeholder’s consultations to assess CSA innovations using four climate-smart performance indicators (productivity, income, adaptation, and mitigation) and four implementation feasibility indicators (technology cost, technical feasibility, gender inclusivity, and market demand). The best-bet CSA innovations included drought- and submergence-tolerant rice varieties, perennial rice, and rice-vegetable rotation in irrigated lowlands; drought-tolerant rice varieties, rice-tuber, rice-vegetable, and rice-legume rotations in rainfed lowlands; drought-tolerant rice varieties and mulching in rainfed uplands; and submergence-tolerant rice varieties, perennial rice, and integrated rice-fish in submergence systems. The average perceived adoption level of CSA innovations by farmers in the rice-growing environments was low, ranging from 7 to 19% due to the lack of finance, technical knowledge, machinery, fertilizer, and quality seeds. Governments, farmers’ organizations, and research and academic institutions were identified as critical actors in the wide spread adoption of CSA innovations. The framework used in this study can be used to identify and invest into locally relevant best-bet CSA innovation packages.